Reflectance anisotropy spectroscopy of Si(111)-(3 x 1)Li and Ag surfaces - MCGILP, JOHN; PATTERSON, CHARLES (My University, 2013)
The Si(111)-(3 × 1)Li and Ag surface structures consist of Si honeycomb chains separated by channels occupied by Li or Ag atoms. The dimerization of neighboring Ag atoms results in a larger c (12 × 2)Ag superstructure. We report calculations of the electronic surface states, dielectric function, and reflectance anisotropy spectrum of these surfaces using hybrid density functional theory (DFT) methods. The positions of surface states and the reflectance anisotropy spectrum calculated using DFT are in very good agreement with experimental results, where they have been reported. The surface states which contribute to the reflectance anisotropy below the band gap are identified for each orientation of the incident electromagnetic field
PUBLISHED
Keywords: Physics